The development of an ICT framework for business intelligence at the Brazilian National Cancer Institute: a case study of organizational learning and innovation - Gonçalves, Antônio Augusto; Barbosa, José Geraldo Pereira (Revista de Administração da UFSM, 2017)
This paper presents the development of an ICT framework for the management, processing and analysis of large-scale Brazilian cancer data. This was a qualitative and descriptive study conducted at Brazilian National Cancer Institute (INCA). The benefits derived from the framework implementation, so far, are: real-time knowledge access; patient’s focus and satisfaction; enhanced knowledge transfer and diffusion of best health care practices; reduction in treatment costs; relief of the INCA’s labor shortage; and finally speediness of cancer diagnosis and enhanced quality of both diagnosis and data used in epidemiological studies. The study also identifies the critical aspects that must be observed by the Brazilian health organizations in early stages of development of BI systems and thus contributes to the faster adoption of such systems.